If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 100m = 110m + 90 Reorder the terms: 100m = 90 + 110m Solving 100m = 90 + 110m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-110m' to each side of the equation. 100m + -110m = 90 + 110m + -110m Combine like terms: 100m + -110m = -10m -10m = 90 + 110m + -110m Combine like terms: 110m + -110m = 0 -10m = 90 + 0 -10m = 90 Divide each side by '-10'. m = -9 Simplifying m = -9
| 10x-5=7x+4 | | q=.5p-5 | | 10n+7=97 | | 10n+7=39 | | (9b-7)-2(4b+1)=-3 | | 3x+2=x+20 | | x^4-20x-8=0 | | 3x-(2x+7)=1 | | 2(13x+4)+7(6x-5)= | | 5x+5x+4+8=6x+4+3x | | 62-6x=12x+24 | | 10-9x=65-44x | | 174-4x=6x+24 | | 8(x+2)=2(3x+4) | | 5(t-5)+4t=50-t | | 2(10-2y)+y=11 | | 3x+12=x | | -3y+8=-4y+2 | | 4+6x=29+x | | 9(x+5)=-3(x-39) | | t=2+1.25c | | -12(x+3)=4(x-21) | | 6p+7=15+5p | | 3x+22=13x-68 | | 7x=6x-462 | | 0=-5+7x+12x^2 | | 15t-6=10t+24 | | 15t-6=10t | | -12(x+6)=3(x-49) | | -12(x+9)=4(x-39) | | 80=w^2+l | | -12(x-1)=3(x+24) |